Interventions to support informal caregivers of people with chronic obstructive pulmonary disease: a systematic literature review - Marques, Alda (2021)
Chronic obstructive pulmonary disease (COPD) imposes tremendous challenges for both patients and informal caregivers. Caregivers are key players in the management of COPD. Recently, COVID-19 further increased reliance on informal caregivers who urgently need specific support. This systematic literature review aimed to systematically describe the content and explore the effects of interventions to support informal caregivers of people with COPD.